A novel hybrid polygeneration system supplying energy and desalinated water by renewable sources in Pantelleria Island. (15th October 2017) - Calise, Francesco; Macaluso, Adriano; Piacentino, Antonio; Vanoli, Laura
Abstract: In this paper a thermoeconomic analysis of a novel hybrid Renewable Polygeneration System connected to a district heating and cooling network is presented. The plant is powered simultaneously by solar and geothermal sources, producing electricity, desalinated water, heat and cooling energy. System layout includes Parabolic Through Collector (PTC) field, geothermal wells, Organic Rankine Cycle (ORC) unit and a Multi-Effect Desalination (MED) system. Cooling and thermal demands are calculated by suitable building dynamic simulation models, calibrated for Pantelleria Island. Electrical demand is obtained by measured data. A detailed control strategy has been implemented in order to prevent any heat dissipation, to match the appropriate operating temperature levels in each component, to avoid a too low temperature of geothermal fluid reinjected in the wells and to manage the priority of space heating and cooling process. A 1-year dynamic simulation has been performed and results analyzed on daily, monthly and yearly basis. The system achieved an SPB equal to 8.50 and it resulted capable to cover the energy demands of a small community. Moreover, the plant is capable to cover the fresh water demand of the Pantelleria Island. Highlights: A dynamic simulation of a hybrid RPS placed in Pantelleria Island is presented. Plant includes ORC, PTC, MED and it is connected to a DHC network. The plant provides power and performs space heating/cooling for a small community. Plant covers entirely the fresh water demands of Pantelleria Island. Pay back period is equal to 8.50 years.